MUCOLYTIC ACTIVITY OF ROSELLE (Hibiscus sabdariffa L.) CALYCES EXTRACT ON COW INTESTINAL MUCUS - Nerdy Nerdy; Kesaktian Manurung (Jurnal Kedokteran Hewan, 2018)
This study aimed to examine the mucolytic activity of roselle calyces extract on cow intestinal mucus in vitro. The extraction of rosellecalyces was performed by the subsequence maceration method using different polarity solvent (n-hexane, ethyl acetate, and methanol). Mucolyticactivity of each extract was evaluated by measuring the viscosity of mixture of cow intestinal mucus and phosphate buffer pH 7 compared toacetylcysteine as the standard mucolytic drug. The result showed that the decreasing of cow intestinal mucus and phosphate buffer pH 7 mixturesviscosity was indicated the increasing of mucolytic activity. The n-hexane, ethyl acetate, and methanol extract of roselle calyces exhibit dosedependentmucolytic activity. Mucolytic activity of roselle calyces ethyl acetate extract with dose of 0.8% and roselle calyces methanol extractwith dose of 0.6% showed no significant difference to mucolytic activity from acetylcysteine with dose of 0.1% (positive control). An increaseddose of roselle calyces extract will decrease the viscosity of cow intestinal mucus and phosphate buffer pH 7 mixtures, indicating an increase inmucolytic activity.